2013
DOI: 10.1016/j.jcma.2013.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of functional outcomes and quality of life in patients with C5 palsy

Abstract: Patients undergoing combined anterior-posterior decompression surgery had the highest incidence of C5 palsy, and correlations between the ARAT, JTHF, EQ-5D visual analog scale clinical tools, and MMT scores supported these findings. Female status and lower decompression levels could also be predictive factors for complete recovery, although additional research is needed to substantiate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…As a large review recently stated, there is no overall statistical difference between anterior or posterior approaches, although some groups describe a significantly higher incidence in posterior procedures[ 21 , 28 ], as reported here. Nevertheless, considering all of the results of the larger studies, there is a trend towards the anterior approach surgeries to represent the safer strategy referring to C5 palsy rates compared to posterior procedures[ 23 ].…”
Section: Discussionsupporting
confidence: 55%
“…As a large review recently stated, there is no overall statistical difference between anterior or posterior approaches, although some groups describe a significantly higher incidence in posterior procedures[ 21 , 28 ], as reported here. Nevertheless, considering all of the results of the larger studies, there is a trend towards the anterior approach surgeries to represent the safer strategy referring to C5 palsy rates compared to posterior procedures[ 23 ].…”
Section: Discussionsupporting
confidence: 55%
“…Bydon et al [ 84 ] reported on comparison between anterior and posterior approaches, the incidence of C5 palsy was significantly higher in the posterior method than the anterior method (8.6% vs 1.6%) ( P <.001). Chang et al [ 40 ] performed another study to compare anterior and posterior approaches. In their study, the incidence of C5 palsy has been reported as 0.7% and 8.8% for anterior and posterior, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] However, a palsy with MMT 2 was sometimes irreversible, 19 and often decreased patients' quality of life and put a burden on their financial status by delaying their return to work after surgery. 18,20 The method employed to diagnose C5 palsy was the MMT, which divides the strength of the muscle into six grades from 0 to 5. Twenty-six out of the 28 included studies reported the risk factors for C5 palsy development (see Table 1).…”
Section: Clinical Featuresmentioning
confidence: 99%